Interactive Quizzes and Games: Enhancing Speaking Skills in English Language Learning - Hairul, Hairul; Rahma Aini; Yeyen Febrilia (Jurnal Teknologi Informasi dan Masyarakat, 2025)
Developing EFL speaking remains challenging in many classroom contexts. This study examined the effect of interactive quizzes and games on eleventh-grade students’ speaking skills in an Indonesian Islamic boarding school. Using a pretest–posttest control group design, 30 students in two intact classes (n = 15 each) received four weeks (16 sessions) of either interactive quiz/game activities or traditional speaking instruction. Speaking performance (pronunciation, vocabulary, grammar, fluency, and accuracy) was assessed using equivalent pre- and post-speaking tests. Shapiro–Wilk tests confirmed normality of difference scores (p > .05). Both groups improved, but gains were larger in the experimental group (pre: M = 36.00, SD = 17.55; post: M = 86.33, SD = 11.10) than in the control group (pre: M = 36.67, SD = 14.96; post: M = 46.67, SD = 24.18). Groups were equivalent at baseline, t(28) = 0.112, p = .912. Posttest scores differed significantly, t(28) = −5.775, p < .001, d = 2.109, indicating a very large practical effect. These findings suggest that interactive quizzes and games can substantially enhance EFL speaking performance compared with conventional instruction.